Mutation in Eth A protein of Mycobacterium tuberculosis conferred drug tolerance against enthinoamide in Mycobacterium smegmatis mc2155. (June 2022) - Anand, Pradeep Kumar; Kumar, Arbind; Saini, Amrit; Kaur, Jagdeep
Abstract: EthA is an NADPH-specific flavin adenine dinucleotide (FAD) containing monooxygenase that activates the –second-line drug ethionamide (ETH). ETH gets converted to an active form after interaction with the EthA (monooxygenase) protein. Upon activation, ETH interacts with NAD+ to form an ETH-NAD adduct, which hampers the activity of InhA (Enoyl-[(acyl-carrier-protein) reductase (NADH)]. This, in turn, inhibits the cell wall synthesis, thus killing the Mycobacterium tuberculosis (Mtb). Mutations in the EthA gene can modulate ETH activation. The mutation at 202 position (Val202-Leu) of EthA protein has been reported frequently in ETH resistance. In this study, the effect of this mutation on the function of the EthA protein was examined through structural and functional analysis. Molecular docking of wild type and mutated EthA protein with ETH were compared to inspect the effect of mutation on molecular mechanism of drug resistant. Docking results corroborated that the lower docking score of the mutant protein, larger binding cavity, and lower affinity towards ETH resulted in a less compact and energetically less stable structure than the wild type protein. The computational outcome was authenticated by in-vitro experiments. The wild type and mutated genes were cloned and expressed in M. smegmatis, a surrogate host. Antibiotic susceptibility testing demonstrated that the mutant showed high growth and survival in the presence of the ETH drug. Overall, the results indicated that a mutation in the intergenic region of EthA protein could result in the altered conversion of ETH to the active form, resulting in differential ETH sensitivity for M. smegmatis carrying the wild type and mutant gene. Graphical Abstract: ga1 Highlights: EthA activates the second-line drug Ethionamide (ETH). Mutations in the EthA gene can modulate ETH activation. The mutation at 202 position (Val202-Leu) of EthA protein has been reported frequently in ETH resistance. Docking and MD studies revealed that mutation in EthA enlarged binding cavity, and lowered its affinity towards ETH.. Antibiotic susceptibility testing demonstrated that the mutant showed high growth and survival in the presence of ETH drug.